Role of a Service Corridor in ICU Noise Control, Staff Stress, and Staff Satisfaction: Environmental Research of an Academic Medical Center. (April 2013) - Wang, Zhe; Downs, Betsy; Farell, Ashley; Cook, Kimberly; Hourihan, Peter; McCreery, Shimby
OBJECTIVE: To investigate the role of a dedicated service corridor in intensive care unit (ICU) noise control and staff stress and satisfaction. BACKGROUND: Shared corridors immediately adjacent to patient rooms are generally noisy due to a variety of activities, including service deliveries and pickups. The strategy of providing a dedicated service corridor is thought to reduce noise for patient care, but the extent to which it actually contributes to noise reduction in the patient care environment and in turn improves staff performance has not been previously documented. METHODS: A before-and-after comparison was conducted in an adult cardiac ICU. The ICU was relocated from a traditional hospital environment to a new addition with a dedicated service corridor. A total of 118 nursing staff participated in the surveys regarding pre-move and post-move environmental comfort, stress, and satisfaction in the previous and new units. Acoustical measures of noise within the new ICU and a control environment of the previous unit were collected during four work days, along with on-site observations of corridor traffic. RESULTS: Independent and paired sample t -tests of survey data showed that the perceived noise level was lower and staff reported less stress and more satisfaction in the new ICU ( p < 0.01). Analyses of acoustical data confirmed that the new ICU was significantly quieter ( p < 0.02). Observations revealed how the service corridor impacted patient care services and traffic. CONCLUSIONS: The addition of a dedicated service corridor works in the new unit for improving noise control and staff stress and satisfaction.